If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 16x = -15 Solving 3 + 16x = -15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 16x = -15 + -3 Combine like terms: 3 + -3 = 0 0 + 16x = -15 + -3 16x = -15 + -3 Combine like terms: -15 + -3 = -18 16x = -18 Divide each side by '16'. x = -1.125 Simplifying x = -1.125
| 5x-4=4-3(5-2x) | | -26=4x-9 | | 21=15a | | 43-2x=-8x | | 3x+1=79 | | 2h+h= | | 5x=297 | | 4x-5=11x-70 | | 8m-(7+5m)= | | x/2-10=x-32 | | http://x/2-10=x-32 | | x^3=96 | | 6y-2=4+3(y+3) | | 3x-10=2+6(5+4x) | | 39c-40=-9 | | -4(1+n)-1=-11(n-4) | | .6u+5.4=.3u+45 | | 2x-2.50=6.50 | | 6(y+9)+5=7y-3 | | 2x-3=x+s | | x^2-8+11=0 | | 9x^2+6x=3x+6 | | 11(9x+2)=-2(3x-11) | | 3(-5b(2/3))=2-7b | | 9s-3=10+4(s+8) | | x-6+9=1 | | 7w-8=1+10(w+4) | | -3x+4=-10+5(-7-x) | | 8m-5+m=67 | | x-6+3=9 | | -1=4+2(1-5x) | | 22=5x-7 |